On the Smoothing of the Square-Root Exact Penalty Function for Inequality Constrained Optimization - Meng, Zhiqing; Dang, Chuangyin; Yang, Xiaoqi (Computational optimization and applications, 2006)
In this paper we propose two methods for smoothing a nonsmooth square-root exact penalty function for inequality constrained optimization. Error estimations are obtained among the optimal objective function values of the smoothed penalty problem, of the nonsmooth penalty problem and of the original optimization problem. We develop an algorithm for solving the optimization problem based on the smoothed penalty function and prove the convergence of the algorithm. The efficiency of the smoothed penalty function is illustrated with some numerical examples, which show that the algorithm seems efficient.